Understanding accounting principles - Marsden, Stephen J. (North Ryde, N.S.W. : CCH Australia, 2012)
Understanding accounting principles is not only designed to assist accountancy students gain an appreciation of key accounting concepts and principles, but is also aimed at those students who do not necessarily require a detailed or in-depth understanding of accounting and wish to go on to become a qualified accountant. The book has been deliberately written using simple language so that readers with a non-accounting background will find it easy to understand. The book is practical in nature and contains numerous worked examples, diagrams, flowcharts and commonly asked questions at the end of each chapter --Back cover.
Introduction to bookkeeping -- Recording transations -- Adjusting entries, closing entries and preparation of the financial statements -- Accounting for GST -- Accounting for cash, debtors and creditors -- Accounting for inventory -- Accounting for non-current assets -- Financial statement analysis.
Includes index.
First published 2011.
Keywords: Bookkeeping -- Australia; Accounting -- Australia; Australian